Strategi Pemasaran terhadap Volume Penjulan Karang Hias Euphyllia Glabrencens di PT Panorama Alam Tropika Jakarta Selatan - Jamila M.Darwis; Sulkifli Sulkifli; Nur Alam Kasim (Pusat Riset dan Inovasi Nasional, 2024)
Marketing is one of the activities in the economy that helps in creating economic value. Economic value itself determines the price of goods and services. Important factors in creating such value are production, marketing and consumption. The purpose of this study is to find out the marketing strategy for sales volume in ornamental coral products (coral) euphyllia glabrencens.The marketing strategy carried out by PT. Panorama Alam Tropika in marketing its products is using a 4P marketing mix marketing mix strategy from the product strategy, namely with coral ornamental coral products that are always of quality, superior, and varied. The place strategy is to choose a strategic location of the company with a company distance close to the airport of 30 ± minutes so that the process of transporting production products is faster and reduces transportation costs. Panorama Tropical Nature has determined the price with the size, type, and quality of ornamental corals (coral). And promotion strategy is to choose a strategic location of the company with a company distance close to the airport of 30 ± minutes so that the process of transporting production products is faster and reduces transportation costs. Panorama Tropical Nature has determined the price with the size, type, and quality of ornamental corals (coral). And promotion strategy by using social media Instagram and Facebook by displaying attractive product photos and still providing special prices (discounts) to customers. The marketing strategy is carried out by PT. South Jakarta Tropical Natural Panorama well and can develop its business in the midst of a lot of competition. Keywords:,